2002
DOI: 10.1021/jp020542y
|View full text |Cite
|
Sign up to set email alerts
|

Calculated OH-Stretching Vibrational Transitions in the Water−Nitrogen and Water−Oxygen Complexes

Abstract: We have calculated the fundamental and overtone OH-stretching vibrational band intensities of the water−nitrogen (H2O·N2) and water−oxygen (H2O·O2) complexes. The calculations use the harmonically coupled anharmonic oscillator local mode model with local mode parameters obtained from scaled ab initio calculations and ab initio calculated dipole moment functions. The H2O·N2 and H2O·O2 complexes are weakly bound and the individual molecular units are only slightly perturbed by complexation, unlike what is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
124
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(137 citation statements)
references
References 55 publications
12
124
1
Order By: Relevance
“…Kjaergaard et al have observed the same inadequacy of DFT in determination of electrostatic moments in systems with hydrogen bonding in the case of the water dimer. 41 Our ab initio calculations predict that trans-perp HOONO has a larger permanent dipole moment than cis-cis HOONO, and one that points predominantly along the c axis of the molecule. The permanent dipole moment in cis-cis HOONO roughly bisects the a and b axes in the plane of the molecule and points towards the terminal O with a slightly larger component along the b axis than the a axis.…”
Section: Calculated Transition Strengths Of Cis-cis and Trans-perpmentioning
confidence: 78%
“…Kjaergaard et al have observed the same inadequacy of DFT in determination of electrostatic moments in systems with hydrogen bonding in the case of the water dimer. 41 Our ab initio calculations predict that trans-perp HOONO has a larger permanent dipole moment than cis-cis HOONO, and one that points predominantly along the c axis of the molecule. The permanent dipole moment in cis-cis HOONO roughly bisects the a and b axes in the plane of the molecule and points towards the terminal O with a slightly larger component along the b axis than the a axis.…”
Section: Calculated Transition Strengths Of Cis-cis and Trans-perpmentioning
confidence: 78%
“…39 More recently, empirically scaled ab initio calculated local-mode parameters combined with ab initio dipole moment function have been successful in predicting OH-stretching spectra of hydrated complexes. 40,41 The advancement in computational methods and hardware now allows high-level ab initio calculations, which can eliminate the need for empirical scaling of the local-mode parameters. For example, the OH-stretching localmode parameters of the different conformers in ethylene glycol were recently calculated with impressive agreement to experiment.…”
Section: Introductionmentioning
confidence: 99%
“…The K p of Vaida and Headrick (2000) shows a peculiar increase, almost linearly proportional to temperature. The K p values of Kjaergaard et al (2002) have a minimum around 225 K and increase at high temperatures, indicating no dissociation of the complex. In both cases the behaviour of K p is not compatible with the estimated structure of the H 2 O-O 2 complex.…”
Section: K P Obtained With the Anharmonic Approachmentioning
confidence: 99%
“…The studies of Vaida and Headrick (2000) and Kjaergaard et al (2002) both used the harmonic oscillator approximation to calculate the partition functions needed to estimate K p . Alternately, Sabu et al (2005) calculated the partition function, and thus K p , using another approach.…”
Section: K P Obtained With the Anharmonic Approachmentioning
confidence: 99%
See 1 more Smart Citation